2017
DOI: 10.1039/c7cp03192k
|View full text |Cite
|
Sign up to set email alerts
|

Importance of non-intrinsic platinum dissolution in Pt/C composite fuel cell catalysts

Abstract: The dissolution of different platinum-based nanoparticles deposited on a commercial high-surface area carbon (HSAC) support in thin catalyst films is investigated using a highly sensitive electrochemical flow cell (EFC) coupled to an inductively coupled plasma mass spectrometer (ICP-MS). The previously reported particle-size-dependent dissolution of Pt is confirmed on selected industrial samples with a mean Pt particle size ranging from 1 to 4.8 nm. This trend is significantly altered when a catalyst is dilute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 58 publications
5
74
0
Order By: Relevance
“…The increase of average crystallite size with electrochemical treatment may be attributed to the growth of larger crystallites by redeposition of dissolved Pt (Ostwald ripening). The larger average particle size for a higher amount of dissolution in the presence of WE2 (≈17 % in the presence of WE2 compared to ≈6 % in the absence of WE2) may be attributed to the faster dissolution of smaller particles leading to an overall higher average particle size. However, the particle growth normalized to dissolution (growth [%]/dissolution [%]) remains significantly lower for the dissolution study in the presence of WE2 (Figure S3 d, Supporting Information), suggesting less redeposition of dissolved Pt on the source particles.…”
Section: Resultsmentioning
confidence: 99%
“…The increase of average crystallite size with electrochemical treatment may be attributed to the growth of larger crystallites by redeposition of dissolved Pt (Ostwald ripening). The larger average particle size for a higher amount of dissolution in the presence of WE2 (≈17 % in the presence of WE2 compared to ≈6 % in the absence of WE2) may be attributed to the faster dissolution of smaller particles leading to an overall higher average particle size. However, the particle growth normalized to dissolution (growth [%]/dissolution [%]) remains significantly lower for the dissolution study in the presence of WE2 (Figure S3 d, Supporting Information), suggesting less redeposition of dissolved Pt on the source particles.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a higher Pt concentration also causes a lower Pt dissolution due to the Nernstian behavior of this reaction. 16,33 In order to get more insight into these mechanisms, another set of experiments (see section Linear sweep anodic scan rate was fixed at 5 mVs −1 followed by potential holds at different lower potential limits (LPL)) was performed.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Those studies have revealed that Pt electrochemical dissolution is predominantly a transient phenomenon occurring due to an interplay of Pt oxidation and reduction. The amount of dissolved platinum can be manipulated via different electrochemical treatments (scan rate, width of anodic and cathodic potential window), 1 gas atmosphere, 12 electrolyte, presence of organic molecules, 6,13 alloying metals, 8,14,15 thickness of the catalyst layer, 10,16 type of support material 16 and, last but not least, by the Pt particle size. 4 Much is owed to the development of advanced on-line analytical tools, especially electrochemical scanning flow cell (SFC) in combination with inductively coupled plasma mass spectrometer (ICP-MS).…”
mentioning
confidence: 99%
“…Recent research on potential dependent transient dissolution of polycrystalline and carbon supported platinum has shed light on the nature of this degradation mechanism . The major results have been the elucidation of anodic and cathodic dissolution triggered by surface oxide formation and reduction, respectively.…”
Section: Introductionmentioning
confidence: 99%